2012
DOI: 10.1021/es304050f
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Occurrence and Distribution of Bisphenol A Diglycidyl Ether (BADGE) and its Derivatives in Human Urine from the United States and China

Abstract: Despite reports of the occurrence of bisphenol A diglycidyl ether (BADGE) and its derivatives in canned foods and consumer products, biomonitoring studies of human exposure to these compounds are lacking. In this study, 127 urine samples collected from the U.S. and China were analyzed for free and total (free plus conjugated) concentrations of BADGE and its three derivatives, bisphenol A (2,3-dihydroxypropyl) glycidyl ether [BADGE·H(2)O], bisphenol A (3-chloro-2-hydroxypropyl) (2,3-dihydroxypropyl) ether [BADG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 32 publications
1
43
2
Order By: Relevance
“…According to the human exposure studies available on BPA-A, equivalent values to those of BPA were found in urine for BPS and BPF, at average levels of about 10 -9 -10 -10 M, (Zhou et al, 2014). BPB and BADGE were detected infrequently and their levels were around 10 -9 M (Cobellis et al, 2009;Cunha and Fernandes, 2010;Wang et al, 2012Wang et al, , 2015Asimakopoulos et al, 2014). The significant BPA-A-induced suppression of testosterone found here occurred for exposure at lower concentrations (generally 10 -6 -10 -8 M) than that observed for BPA.…”
Section: Inhibin Bmentioning
confidence: 99%
“…According to the human exposure studies available on BPA-A, equivalent values to those of BPA were found in urine for BPS and BPF, at average levels of about 10 -9 -10 -10 M, (Zhou et al, 2014). BPB and BADGE were detected infrequently and their levels were around 10 -9 M (Cobellis et al, 2009;Cunha and Fernandes, 2010;Wang et al, 2012Wang et al, , 2015Asimakopoulos et al, 2014). The significant BPA-A-induced suppression of testosterone found here occurred for exposure at lower concentrations (generally 10 -6 -10 -8 M) than that observed for BPA.…”
Section: Inhibin Bmentioning
confidence: 99%
“…It is clearly established by empirical data that FCCs can migrate from food contact materials and articles into food, indicating a high probability that a large majority of the human population is exposed to some or many of these chemicals [3]. Indeed, for some FCCs there is evidence for human exposure from biomonitoring [4][5][6][7][8][9][10][11], although some FCCs may have multiple uses and also non-food contact exposure pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, it mimics estrogen. Moreover, BPA can arouse many additional health problems, including weight gain, early-onset of puberty, infertility, behavioral changes, cardiovascular effects and diabetes (Morgan et al, 2011;Johnson et al, 2012;Wang et al, 2012).…”
Section: Health Effects Of Bpamentioning
confidence: 99%